Genotoxicity testing of food additives by employing Vicia MN assay - Kumari, Nishi; Abha, Abha; Jha, Anand M (Journal of Phytology, 2012)
In the present study genotoxic effect induced by two food preservatives viz. ammonium acetate and zinc acetate was evaluated in the root meristem cells of Vicia faba. Genotoxic property was evaluated by scoring micronucleus in the root tip cells of treated roots. Roots were treated with 1, 2.5. 5, and 7.5 g/l of ammonium acetate and zinc zcetate solutions at room temperature in dark for 6, 12, 18 and 24h. The dosages selected for evaluation were below LD50 dose of the compounds. The increase in the concentration and period of treatment of each compound resulted in increase in the frequency of micronuclei. The results indicate that ammonium acetate and zinc acetate induce genotoxic effect in the dose range tested.